“Go to our brethren, the Haytians”: Haiti as the African Americans’ Promised Land in the Antebellum Era - (:unkn) unknown (My University, 2015)
In the antebellum era, although some prominent African American leaders were firmly opposed to emigration and vocally denounced the American Colonization Society and its African project, others did advocate relocation to different and closer places. This article examines the genesis and the rise of the “Haitian propaganda” that climaxed in the 1850s, and ultimately culminated in the actual emigration of several thousand African Americans to Haiti between 1859 and 1862.
Keywords: African Research